Multidrug Resistance Phenotype: A Potential Marker of Chemotherapy Resistance in Breast Cancer?. Issue 9 (6th January 2016) - Unknown
Abstract : Laboratory markers help medical oncologists predict chemotherapy resistance. The multidrug resistance gene (MDR1) and its P-glycoprotein product (MDR1) hold the promise of being such a marker. The only studies that have correlated the expression of MDR with clinical response to chemotherapy have used immunohistochemical reactions on tissue sections with monoclonal antibodies to MDR1. We have conducted such a study with a polyclonal antibody. The presence of MDR1 in our study did not define a population of chemotherapy- resistant patients. Correlative laboratory and clinical studies need to be performed to define the role of MDR in human breast cancer.